Unravelling the Entrepreneurial Ecosystem: Actors and Factors Shaping Agricultural MSMEs in Indonesia - Zaki, Ahmad; Koraag, Satrio Tegar Gunung; Kusumawardhani, Mawar (RSF Conference Series: Business, Management and Social Sciences, 2025)
Agricultural micro, small, and medium enterprises (MSMEs) play a vital role in Indonesia’s rural economy and food security, yet they face persistent structural challenges, including limited access to finance, weak infrastructure, and fragmented policy support. These constraints hinder their growth and resilience, particularly in rural areas. This study aims to examine the key actors and contextual factors shaping the entrepreneurial ecosystem (EE) of agricultural MSMEs in Indonesia, in order to identify strategic interventions that support sustainable and inclusive development. Using a qualitative approach, this research synthesizes data from peer-reviewed literature, official reports, and credible digital sources. The analysis is guided by the entrepreneurial ecosystem framework and network theory, applying thematic analysis to uncover actor-factor dynamics. The findings reveal a vibrant but uneven ecosystem, where strong local networks and community-market linkages are offset by low digital adoption, weak government engagement, and insufficient financial access. Infrastructure gaps and limited entrepreneurial literacy further constrain innovation and competitiveness. The study makes a conceptual contribution by contextualizing EE frameworks within Indonesian agriculture and integrating sustainability and inclusivity dimensions. Practically, it proposes policy reform, targeted digital inclusion, and rural infrastructure enhancement to empower women, youth, and smallholder entrepreneurs.